The Influence Of Population, Economic Growth, Government Expenditure On Regional Income (PAD) In South Sulawesi Province - Yulianti Yulianti; Basri Bado; Irwandi Irwandi; Sri Astuty; Regina Regina (Pusat Riset dan Inovasi Nasional, 2026)
The objective of the provision of regional autonomy is to diminish the reliance of local administrations on the central government, particularly with regard to financial matters, thereby enabling regions to finance their own operations independently. The objective of this study is to ascertain the impact of population, economic growth, and government expenditure on Regional Original Income (PAD) in South Sulawesi Province. The present study constitutes a quantitative investigation, utilising secondary data from BPS with panel data, constituting time series data for the period 2019-2023, in conjunction with cross-section data from six regencies/cities. In light of the findings from the empirical investigation, it is concluded that the most suitable estimate to be employed in this study is the Common Effect Model (CEM). The findings indicate that all independent variables, namely population, economic growth, and government expenditure, collectively exert a substantial influence on regional original income in South Sulawesi Province. Meanwhile, the results of the t-test demonstrate that the population variable has a probability value of 0.0000, which is less than 0.05. It can be concluded that the population has a positive and significant effect on regional original income in South Sulawesi Province. Moreover, the probability of economic growth is determined to be 0.2502, which is greater than 0.05. This indicates that it exerts minimal influence on regional original income in South Sulawesi Province. Subsequently, the probability value of government expenditure is determined to be 0.0355, which is less than 0.05. This finding indicates that government expenditure exerts a positive and significant influence on local revenue in South Sulawesi province.